The Urgency and Functions of Arabic Language Learning in Educational Institutions - Fathur Rusydi Amar (International Journal of Language and Ubiquitous Learning, 2023)
Background. This research explores the background of the importance of learning Arabic, a Semitic language with over 280 million speakers as a first language. Influenced by aspects of religiosity and internationality, Arabic has a significant role in culture, Islamic religion and international relations. Purpose. This research aims to understand the role and urgency of Arabic in a global context, covering religious, cultural and diplomatic aspects. It aims to analyze the development of the Arabic language from historical aspects to contemporary developments, as well as identify its impact as an international language involving non-Muslims. This research also intends to explore a deeper understanding of the importance of learning Arabic outside the religious context, focusing on its functional diversity and use in the modern world. Method. The research method involves literature analysis, Arabic language learning needs survey, and implementation case studies in educational institutions to understand the urgency and function of Arabic language learning. Results. The importance of learning Arabic for Muslims is reflected in three main aspects: the understanding of Islamic teachings, the unification of Muslims, and human civilization. Arabic is the main source of knowledge, especially in understanding Islamic religious sources. Moreover, it plays a key role in uniting the global Muslim community, facilitating communication and enhancing unity. Conclusion. There are many benefits that will be gained if Muslims learn Arabic. Among them, first, fahmul Islam (understanding Islamic teachings). By mastering Arabic, of course it will be very easy for us to understand most of Islamic teachings. Because the sources of Islamic teachings (the Koran, hadith, and books written by ulama) use Arabic. Allah SWT said, "Indeed, We made the Qur'an in Arabic so that you understand.